Democracy, public temporality and Judiciary: reflections on contemporary judicialization of politics in democratic governments - Machado, Igor Suzano (2014)
The interference of Judiciary in politics has attracted criticisms for being an “undemocratic” practice that would give excessive power to politicians not elected by vote. Our hypothesis is that the interference of Judiciary in politics does not necessarily mitigates democracy, being able, in certain situations, of making democracy “more democratic”. For that, however, it is necessary, first, to demonstrate that the decisions taken by elected political bodies under the majority rule do not exhaust the democratic government, and, secondly, that, in this way, nothing, in principle, prevents Judiciary to make the “people’s government” more accessible to a larger portion of the people. With that in mind, this paper argues that the possibility of Judiciary be a democratic agency lies on its capacity of preserving what François Ost calls, referencing the notion of public space, a “public temporality”.